IMPLEMENTASI KONSEP 4C DALAM PEMBELAJARAN PADA MATA KULIAH ANALISIS KEBIJAKAN PENDIDIKAN - Azwar Anas; Endin Mujahidin (TADBIRUNA: Jurnal Manajemen Pendidikan Islam, 2022)
In the 21st century, students must have skills and develop their potential, so that they become successful individuals and develop in their lives. Among the 21st century skills are 4C skills (Critical thinking, communication, collaboration, creativity). There are many opinions about what 21st century skills are, one of which is the 4C (Critical thinking, Creativity, Collaboration, and Communication). Critical thinking is all about problem solving skills. Creativity is about thinking outside the box, trying new approaches to getting things done, innovation, and invention. Collaboration is the skill of how someone works together, synergizes with each other, adapts in various roles with others to achieve common goals. Communication is a person's skill to convey and share their thoughts, questions, ideas and solutions in the best possible way. This paper will describe these various skills in order to provide additional insight and skill development so that they can be useful in preparing students to face the inevitable changing times